Overhead Transmission Line Easement and Right-of-Way Cases in Crete, Greece: A Statistical Analysis of 1220 Cases from 1974 to 2019 - Pylarinos, D. (Engineering, Technology & Applied Science Research, 2020)
Overhead Transmission Lines (OTLs) are used to carry High Voltage (HV) between HV substations, usually constructed at long distances from each other, thus spanning across numerous different properties. Easements, a legal term for nonpossessory rights, are essential to the utilities in order to maintain a Right-Of-Way (ROW) for construction and maintenance purposes in a corridor of land underneath the lines, and also to enforce certain restrictions within that corridor, in order to ensure the safety of both the OTLs and the public. The exact details of ROW corridors’ management vary between countries as the legislation and each utility’s approach may differ. This paper focuses on 1220 easements/ROW cases regarding the isolated HV Transmission System of the Greek island of Crete from 1974 to 2019. The various related factors are discussed and a statistical analysis of the records is performed.